Microstructure evolution in strontium titanate Investigated by means of grain growth simulations and x-ray diffraction contrast tomography experiments - Syha, Melanie (KIT Scientific Publishing, 2014)
Understanding the physical processes during fabrication and annealing of ceramic materials is a long sought goal among material scientists. Using strontium titanate as a model system for perovskite ceramics, the present work combines advanced non-destructive 3D characterization techniques and computational modeling of microstructure evolution in order to link grain morphology, interface anisotropy and microstructure evolution to macroscopic physical properties .
English
Keywords: Kornwachstum; Röntgenbeugung; Mikrostrukturentwicklung; grain growth; Perowskit; Simulation; micorstructure evolution; strontium titanate; Strontiumtitanat; tomography; simulation